Uji Bahan Nabati Sebagai Rodentisida Alami Terhadap Tikus (Rattus norvegicus) Jantan - Muhammad Nova Alfarisy; Tuti Heiriyani; Riza Adrianoor Saputra (Agroekotek View, 2019)
Rats are pest that often  interfere with farmer’scorps. Damage to agriculture crops caused by rats in field from the pre-harvest, harvest, and post-harvest stage. Rats pest control whichis usually done by darmers by using chemical rodenticide. Chemical rodenticide certainly have an efffect to the enviromental such as living residues. Therefore rodenticide are enviromentally friendly which do not leave a residues. The purpose of this study was to determine the application of natural rodenticide of intoxicating yam, jatropha seed, billigoat weed in controlling male rattus norvegicus and to find the best natural rodenticide. This study was held in Rumah Boni Banjarbaru, South Borneo from april to may 2019. This study used a completely randomized design (CRD) of one factor with 4 treatments and 5 repIications. So that 20 experimentaI units were obtained. The result show that rodenticide apllication very significantly affected the time of death, body weight, and the number of feeds eaten. This study statae that natural rodenticidal jatropha seed were able to control male rattus norvegicus.